2019
DOI: 10.1007/s12649-019-00595-z
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Mesophilic and Thermophilic Mixed Microbial Consortia for Syngas Biomethanation: The Role of Kinetic and Thermodynamic Competition

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…In fact, species belonging to Methanothermobacter sp. genus have been reported to be capable of autotrophic growth and were added to AD system to improve the syngas biomethanation process by enhancing the biomass conversion efficiency and the CH 4 content of the evolved gases 61 . Similarly, Methanbrevibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, species belonging to Methanothermobacter sp. genus have been reported to be capable of autotrophic growth and were added to AD system to improve the syngas biomethanation process by enhancing the biomass conversion efficiency and the CH 4 content of the evolved gases 61 . Similarly, Methanbrevibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Some researchers reported that thermophilic conditions presented a higher CH 4 production rate and H 2 bioconversion rate in H 2 addition reactors (Figeac et al, 2020;Grimalt-Alemany et al, 2020;Yun et al, 2017;Zhu et al, 2019b). In BES, Methanobacterium and Methanobrevibacter prevailed (Geppert et al, 2016).…”
Section: Predominant Methanogens In Upgrading Technologiesmentioning
confidence: 99%
“…The enrichment cultures used as inocula in experiments carried out under mesophilic and thermophilic conditions corresponded to two different MMC previously enriched under mesophilic and thermophilic conditions, respectively. Both enriched cultures originated from the same initial mixture of anaerobic sludges and were enriched using a synthetic syngas mixture as the only carbon and electron source as described in Grimalt-Alemany et al [24].…”
Section: Medium Composition and Mixed Microbial Culturesmentioning
confidence: 99%
“…The calibration (parameter estimation) and validation of the models were performed largely based on a dataset from previous work [24] consisting of one experiment with syngas and 4 specific activity tests with either only CO, H2/CO2 or acetate as the only substrates combined with the methanogenic inhibitor sodium 2bromoethanesulfonate (BES). This dataset was extended with 4 additional experiments, where the initial PH2 was fixed to 1 atm and the initial PCO varied from 0.2 atm to 0.8 atm.…”
Section: Medium Composition and Mixed Microbial Culturesmentioning
confidence: 99%